At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Connect with professionals ready to provide precise answers to your questions on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Answer:
Multiply x + y = 3 by 3 and add it to -3x - 2y = -7
Step-by-step explanation:
When using elimination to solve a system of equations, you multiply one equation by some number. The reason for doing this is that when you add it to the second equation, you want one variable to cancel out. When one variable cancels out (in this case x), you can solve for the other variable (in this case y). I will show this:
3(x + y = 3) = 3x + 3y = 9
3x + 3y = 9
+ -3x + -2y = -7
---------------------------
y = 2
Now, knowing that y = 2, you can substitute y=2 into either equation to solve for x.
-3x - 2(2) = -7
-3x -4 = -7
-3x = -3
x = 1 | to double check (1, 2) as your answer plug these values into both equations
Finding this solution would not have been possible if not for cancelling out the x's above. The other three are wrong because none of the other options cancels out one of the variables.
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.